1970
DOI: 10.1111/j.1365-2672.1970.tb02242.x
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Computer Program for the Statistical Analysis of Heat Resistance Data Applied to Bacillus stearothermophilus Spores

Abstract: Summary. A digital computer program is described which fits log‐linear regression lines to survival curves and thermal destruction time lines and performs appropriate statistical tests. The use of the program is illustrated with heat resistance data from 4 strains of B. stearothermophilus spores at 8 time–temperature relationships. D, F, zD and Q10 values were calculated by the computer program. The heat resistance of the strains was in the order of B

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…These were performed as described by Mallidis & Scholefield (1985) using a capillary tube method and a solid heating block at 120°C. Medium YPTD AAM TS DTA YPTD-S AAM-S TS-S DTA-S YPTD-CH AAM-CH PH 6.5, 7.3 6.5, 7.3 6.9, 7.3 6.8, 7.3 6.5, 7.3 6.5, 7.3 6.9, 7.3 6.8, 7.3 6.5, 7.3 6.5, 7.3 Survivor curves were constructed and statistical analysis on the linear portions of the survivor curves was performed by using a computer program (Navani et at. 1970).…”
Section: H E a T R E S I S T A N C E Testssupporting
confidence: 84%
See 1 more Smart Citation
“…These were performed as described by Mallidis & Scholefield (1985) using a capillary tube method and a solid heating block at 120°C. Medium YPTD AAM TS DTA YPTD-S AAM-S TS-S DTA-S YPTD-CH AAM-CH PH 6.5, 7.3 6.5, 7.3 6.9, 7.3 6.8, 7.3 6.5, 7.3 6.5, 7.3 6.9, 7.3 6.8, 7.3 6.5, 7.3 6.5, 7.3 Survivor curves were constructed and statistical analysis on the linear portions of the survivor curves was performed by using a computer program (Navani et at. 1970).…”
Section: H E a T R E S I S T A N C E Testssupporting
confidence: 84%
“…A variety of media have been used by different workers for the recovery of B. stearothermophilus subjected to heat treatments in research studies or for the sterility testing of cans. Fields (1963), Rotman &Fields (1969) andNavani et al (1970) siearothermophilus on antibiotic assay medium and DTA and also studied the effect of starch, charcoal and furfuraldehyde on recovery, together with the effects of pH and incubation temperature. De Guzman et a/.…”
mentioning
confidence: 99%
“…The thermal resistance of aqueous suspensions of B. stearothermophilus as characterized by D and z values confirmed other work (2,7,11,17,18,24), indicating that these spores are extremely heat resistant and that a 12D process for C. botiulinum would not provide a SD process as used for B. stearothermophilus (D. J. Goeke, paper presented at the Second Annual Eastern Research Highlights Conference, National Canners Association, Washington, D.C., 1977). The z value reported in our study was 8.3°C, whereas a range of 6.9 to 7.8°C has been reported for various strains of B. stearothermophiluis (17).…”
Section: Discussionsupporting
confidence: 72%
“…The influence of the recovery media on heat resistance was studied for other sporeformers. While some authors reported that D values were not modified by the recovery media (Navani et al 1970;Mallidis and Scholefield 1986;Gonzilez et al 1991), others found differences between the 1968; Odlaug and Pflug 1977;Gurney and Quesnel 1980;Zechman and Pflug 1991).…”
Section: Introductionmentioning
confidence: 96%